Elevated brain manganese induces motor disease by upregulating the kynurenine pathway of tryptophan metabolism - Anna S. Warden; Nishant Sharma; Steven Hutchens; Chunyi Liu; Noah R. Haggerty; Kerem C. Gurol; Thomas Jursa; Donald R. Smith; Roy Dayne Mayfield; Somshuvra Mukhopadhyay (Proceedings of the National Academy of Sciences, 2025)
Elevated brain levels of the essential metals manganese (Mn), copper, or iron induce motor disease. However, mechanisms of metal-induced motor disease are unclear and treatments are lacking. Elucidating the mechanisms of Mn-induced motor disease is particularly important because occupational and environmental Mn overexposure is a global public health problem. To address this, here we combined unbiased transcriptomics and metabolomics with functional studies in a mouse model of human environmental Mn exposure. Transcriptomics unexpectedly revealed that Mn exposure up-regulated expression of metabolic pathways in the brain and liver. Notably, genes in the kynurenine pathway of tryptophan metabolism, which produces neuroactive metabolites that impact neurological function, were up-regulated by Mn. Subsequent unbiased metabolomics revealed that Mn treatment altered kynurenine pathway metabolites in the brain and liver. Functional experiments then demonstrated that pharmacological inhibition of the first and rate-limiting step of the kynurenine pathway fully rescued Mn-induced motor deficits. Finally, elevated Mn directly activates hypoxia-inducible factor (HIF) transcription factors, and additional mechanistic assays identified a role for HIF1, but not HIF2, in regulating expression of hepatic kynurenine pathway genes under physiological or Mn exposure conditions, suggesting that Mn-induced HIF1 activation may contribute to the dysregulation of the kynurenine pathway in Mn toxicity. These findings (1) identify the upregulation of the kynurenine pathway by elevated Mn as a fundamental mechanism of Mn-induced motor deficits; (2) provide a pharmacological approach to treat Mn-induced motor disease; and (3) should broadly advance understanding of the general principles underlying neuromotor deficits caused by metal toxicity.